INFLUENCE OF IRRIGATION RATES, FERTILIZERS AND STIMULATORS ON THE YIELD OF GOJI BERRIES (LYCIUM BARBARUM L. AND LYCIUM CHINENSE MILL.) IN UZBEKISTAN (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article presents the results of a study aimed at assessing the efficiency of Goji berry cultivation in Uzbekistan. To date, there is a limited amount of data on genetic resources, selection methods, phytotechnologies and modern approaches to rapid plant propagation using stimulants to increase their productivity. The study examined various irrigation regimes, methods of fertilization, and the effect of biostimulants on crop yield and productivity. Optimal irrigation rates were determined, including volumes of 900, 1200, 1500, and 2000 m³ of water. The best results were achieved with irrigation volumes of 1500 and 2000 m³. Organic fertilizers were applied at a rate of 6.0 t/ha and biohumus fertilizers at a rate of 1.7 t/ha. Biohumus fertilizers demonstrated the greatest efficiency among them. To improve the quality of Goji fruits, growth stimulants were used - Gibberellin and "Ghana Plus", which contributed to the improvement of their quality characteristics.